Italys Privatization Process and Its Implications for China - Bernardo Bortolotti (Fondazione Eni Enrico Mattei (FEEM), 2005)
This report provides an overview of the causes and consequences of the Italian State-owned Enterprises (SOE) reform process. Particularly, it analyzes the symbiotic link between share issue privatization (SIP), i.e. privatization in public equity markets, and financial market development, and shows how the sustained policy of sales has jumpstarted the Italian domestic stock market. Based on the Italian and international experience, the report provides some possible guidelines and policy recommendations in order to achieve the same goal in the Peoples Republic of China (PRC).
Keywords: L33; L30; O16; G14; 330; State-owned enterprises; Share issue privatization; Financial development; Italy; China; Privatisierung; Öffentliches Unternehmen; Vergleich; Italien; China